System design of Pintrich's SRL in a supervised-PLE platform: a pilot test in higher education. Issue 2 (17th February 2023) - Xu, Xiaoshu; Zhu, Xiaoshen; Chan, Fai Man
ABSTRACT: Personal Learning Environment (PLE) represents a shift of learning paradigm towards learner-centered pedagogy, where users become masters of their own learning. PLEs are best used by learners with Self-regulated Learning (SRL) abilities. Previous research showed that learners felt lost or socially isolated in PLEs due to their limited SRL abilities. To increase the accessibility of the PLEs, this research used IDEF0 to analyze the system design of Pintrich's SRL in a PLE platform. A supervised-PLE platform was developed with International English Language Test (IELTS) as its subject matter and was pilot-tested for two years in one of the largest comprehensive universities in East China. Distance Education Learning Environments Survey (DELES) was carried out among 285 learners to test their perceptions of the PLE-IELTS platform and MOOC engagement scale (MES) survey was used among 96 learners to diagnose their engagement on the platform. The DELES survey result showed that the majority of the respondents were positive towards the PLE platform. MES survey result indicated an active engagement on the platform, with cognitive engagement scored the highest compared to social engagement as the lowest. Future research on the system design of the SRL in the PLE platform was suggested.